COMPARISON OF THE EFFECTIVENESS OF MYOFASCIAL PAIN REDUCTION USING LOW-INTENSITY LASER AND RED LED LIGHT THERAPY IN PATIENTS WITH TEMPORO¬MANDIBULAR JOINT DYSFUNCTION - Shynchukovskyi, Igor (Eastern Ukrainian Medical Journal, 2024)
Introduction: Today, there is a significant prevalence of temporomandibular joint (TMJ) dysfunction, which currently ranges from 21.5 % to 50.5 %. This disease can worsen the patient’s quality of life due to the presence of pain, which is the main symptom of this pathology. To reduce the intensity of pain in patients with TMJ dysfunction, low-level laser and red LED light therapy is used. There are a significant number of studies proving clinical efficacy in alleviating the symptoms of TMJ dysfunction using various methods of light therapy, but the number of studies comparing the effectiveness of different light therapy options among themselves is quite limited. The aim of the study was to compare the effectiveness of pain relief and the number of trigger points in patients with TMJ dysfunction using a low-level laser and red LED light. Materials and methods: 60 patients were randomised into 2 groups. Randomisation for patient allocation was performed using Microsoft Excel 2016. Patients of group I received red LED light therapy, radiation sources were applied to the trigger points of the masticatory muscles extracorporeally for 5 minutes. Patients in group II received low-intensity laser therapy for 30 seconds on the trigger points of the masseter muscles extracorporeally. Patients in both study groups received therapy weekly for 4 weeks. The effectiveness of the treatment was assessed by filling out a visual analogue scale (VAS), the number of trigger points of the masticatory muscles and the force of contraction of the masticatory muscles at rest and during tooth contact in patients with temporomandibular joint dysfunction. Results: the VAS scores in group I decreased by 47.02 % from the start of treatment, in group II – by 53.7 %. The number of trigger points in the projection of the masticatory, temporal muscles and parotid region in group I decreased by 62.34 %, in group II – by 72.21 %. According to electromyography, in group I, the amplitude of bioelectrical impulses of the masticatory muscles at rest decreased by 20.58 % on average, and in the state of voluntary teeth clenching – by 22.89 %. In group II, the amplitude of bioelectrical impulses of the masticatory muscles at rest decreased by 25.58 % on average, and in the state of voluntary teeth clenching – by 28.37 %. Conclusions: red LED light therapy and low-level laser therapy reduces pain intensity and the number of trigger points in patients with myofascial pain. Comparison of the effectiveness of red LED light therapy and laser therapy in reducing pain syndrome showed a higher ability of laser therapy to reduce myofascial pain and the number of trigger points in patients with temporomandibular joint dysfunction (p<0.01).